Dynamics of Ebola RNA Persistence in Semen: A Report From the Postebogui Cohort in Guinea. (14th March 2017) - Subtil, Fabien; Delaunay, Charlotte; Keita, Alpha Kabinet; Sow, Mamadou Saliou; Touré, Abdoulaye; Leroy, Sandrine; Msellati, Philippe; Magassouba, N'Fally; Baize, Sylvain; Raoul, Hervé; Ecochard, René; Barry, Moumié; et al.
Abstract: This study modeled the presence of Ebola virus RNA in the semen of male Ebola survivors participating in the Postebogui study in Guinea. The median time of reverse-transcription polymerase chain reaction negativity was 46.4 days after symptom onset (95% confidence interval, 11–82.6). The results emphasize the importance of the World Health Organization recommendations for survivors' management.